Miocene Provenance Changes in Taiwan Caused by Southward Input of Sediments From East China Sea Basin - Fu, Xiaowei; Hu, Lichen; Zhu, Weilin; Huang, Xiangtong; Feng, Kailong; Zhou, Zengyuan (Frontiers in Earth Science, 2022)
The Cenozoic sediments in marginal basins of East Asia ultimately reflected coupling between the tectonics, landscape evolution and drainage reorganization. Recently, provenance of Miocene sediments in the East China Sea Basin (ECSB) and Taiwan has been in hot debate and several models were proposed to interpret the provenance changes. Most of them are related to river reorganization in East Asia and highly relied on detrital zircon U-Pb dating. In this paper, a large number of detrital zircon U-Pb ages of Miocene sediments from ECSB, Taiwan region and the potential source areas have been complied for quantitative provenance analysis. The results suggested that all the early-middle Miocene sediments in Taiwan and ECSB were closely linked to North China and the Korea Peninsular. Over 80% sediments in Taiwan were delivered from the ECSB whose sediments were predominantly contributed by North China and the Korea Peninsular (70%). However, for the late Miocene to Quaternary sediments in ECSB, the contribution of Yangtze River system was 72%, which indicates distinct reorganization of river networks and initial formation of the Yangtze River in the late Miocene. The quantitative provenance analysis together with southward environmental changes from dominantly fluvial sediments in northern and middle ECSB to shallow marine sediments in Taiwan region suggested that the early-middle Miocene sediments of Taiwan was mainly sourced from the North China and the Korea Peninsular by passing the ECSB. Thus, these sediments in Taiwan region would experience river-delta-shallow marine route from ECSB to Taiwan region.